Dominica. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Dominica during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as safety, leadership, good agricultural practices, health and safety, public policies, production, costs, organic agriculture. , food security, inclusion of women and onion production.